The Tubau: symbol of unity / Zalia. A, Harrison Arifin Abdullah and Harozila Ramli - A, Zalia; Abdullah, Harrison Arifin; Ramli, Harozila (Division of Research and Industry Linkages , UiTM Melaka, 2014)
The Tubau 's I production by the Irranun ethnic of Kota Belud, Sabah, is a hand woven cloth which is having a square shape figure interlaced with the symmetrical patterns. The Tubau represents the superfluous skill, aesthetic capability, impressive creativity and the personal expression of the weaver. The Tubau constituted with different types of motifs that were inspired by the environments, which is also, has provided the source of raw materials for the weaving tools. Today, the production of Tubau still is requiring the same skills, techniques and technology as it was produced before. The skilful and experienced weavers, who have been inheriting the weaving skills from the family legacy, is able to produce the Tubau within a short period of time and freely modify and creates the Tubau designs during the entire process of weaving undertaken. The basic designs principle of the Tubau is to have the patterns with variety of colors and the patterns must be able to occupy the whole space of-the-Tubau:-The Tubau-is-strikingly-possessing-its-own-uniqueness-and-special characteristics has been widely accepted and used by other races; thus it has become a tool for unity among the various ethnics and races in Sabah. The Tubau is not exclusively used as a completeness item to the traditional costumes, but it constituted numerous interpretations of significant meanings and philosophy behind its intricate designs. The Tubau also significantly reflects the social system, culture, and the beliefs of the some ethnic groups in Sabah.